Integrated Project Management and Control First Comes the Theory, then the Practice - Vanhoucke, Mario (Springer eBooks, 2014)
This book presents an integrated approach to monitoring projects in progress using Earned Value and Earned Schedule Management combined with Schedule Risk Analysis. Monitoring and controlling projects involves processes for identifying potential problems in a timely manner. When necessary, corrective actions can be taken to exploit project opportunities or to get faltering projects back on track. The prerequisite is that project performance is observed and measured regularly to identify variances from the project baseline schedule. Therefore, monitoring the performance of projects in progress requires a set of tools and techniques that should ideally be combined into a single integrated system. The book offers a valuable resource for anyone who wants to understand the theory first and then to use it in practice with software tools. It is intended for students, professionals and academics with an interest and/or experience in running projects as well as for newcomers in the area of project control with a basic grasp of the Earned Value, Earned Schedule and Schedule Risk Analysis concepts.